Mean Platelet Volume and Ischemia Modified Albumin Levels in Cord Blood of Infants of Diabetic Mothers - Naci Topaloğlu; Şule Yıldırım; Mustafa Tekin; Nazan Kaymaz; Funda Tütüncüler; Cem Özdemir; Emine Coşar (Elsevier, 2014)
Gestational diabetes mellitus (GDM) is a risk for the health of both the pregnant women and her infant. Its unfavorable effects start in utero and continue after birth. It is known that GDM increases oxidative stress and decreases antioxidant enzyme activities. In this study we aimed to investigate cord blood mean platelet volume (MPV) and ischemia-modified albumin (IMA) levels of infants of diabetic mothers (IDM). Methods: Twenty-nine pregnant women with GDM between 37 and 41 gestational weeks who gave birth by spontaneous vaginal delivery were enrolled as study participants together with 20 healthy pregnant women as a control group. Weight, length, and head circumference of babies were measured by the same standard tape immediately after birth. Five milliliters of umbilical venous blood were obtained to study MPV and IMA levels. Results: There was statistically significant difference in levels of MPV (p = 0.037) and IMA (p < 0.001) between groups. They increased in IDM compared with their healthy peers. Conclusion: Evaluation of MPV and IMA together is useful for representing the potential oxidative stress of IDM.